Türk sinemasını besleyen romanlar (1922-1946) - Kale, Özlem (My University, 2009)
Bu tez, üç bölümden oluşmaktadır. Birinci bölümde edebiyat – sinema ilişkisi üzerine teorik bilgiler verilecek; ikinci bölümde seçilen eserlerin ilk sinema uyarlamalarıyla karşılaştırmalı incelemeleri yapılacak; üçüncü bölümde ise sinemaya uyarlanan romanların kazanç ve kayıplarının neler olduğunun belirlenmesine çalışılacaktır.

This thesis called “The novels that enrich the cinema” aims at finding reasons behind changes between novel and movie, figuring out the earns and loses of esthetic values of novels while adaptation, values added to the Turkish cinema by novels, and also reasons that guided moviemakers towards novels by which criteria. In this work, novels of the Republican period up to 1946 which is presumed the turning point for not only Turkish but also world cinema. There are seventy one novels looked into and these books were written between 1922 - 1946 and adapted to the cinema. These novels are thematically sorted out and one out of each subject is comperatively analyzed with a film to set a sample. This thesis is consisted of 3 volumes, first of which deals with theoretical information on the matter of fiction-movie. The second holds analysis of a sample fiction and a movie. The third chapter concludes the values earned and lost during adaptation.
Keywords: Roman; Sinema; Türk Dili